Wage Differentials and International Trade in Italy Using Individual Micro Data 1991-1996 - Anna M. Falzoni; Alessandra Venturini; Claudia Villosio (Institute for the Study of Labor (IZA), 2004)
In this paper we use individual micro data on workers combined with industry and regional data to study the dynamics of the wage differential between skilled and unskilled workers in Italy in the period 1991-1996. Being different to previous empirical studies, our data allow us to explore in a unique framework, the role of all the factors indicated in the literature as possible causes of the widening of the wage gap between skilled and unskilled workers: changes in the individual characteristics of workers, changes in the institutions of the labour market, in skill-biased technological progress and increasing international integration. Our results show that individual, firm and macro variables matter in explaining wage differentials. In particular, international integration, both in terms of trade in goods and in terms of international labour mobility, plays a role in determining the wage differential between skilled and unskilled workers, but the impact is in opposite directions. While, on the one hand, increasing trade in goods reduces wage differentials (through a positive impact on the wages of the unskilled workers), on the other hand immigration increases wage differentials, affecting the wage of the unskilled. As for the role of trade in goods, it is interesting to note that export growth has a positive impact on the wages of the blue collar workers and has no effect on the wages of the white collars, supporting the idea that Italy is atypical with respect to other industrialised countries and has a comparative advantage in low-skilled labour-intensive production. We have also shown that an analysis of the wage differentials hides their different effects on the white and blue collar wage dynamics of the explicative variables.
Keywords: J31; O33; F4; 330; wage differential; institutions; individual characteristics; migration; trade liberalization and skill-biased technological change; Lohnstruktur; Qualifikation; Aussenwirtschaft; Technischer Fortschritt; Internationale Arbeitsteilung; Globalisierung; Schätzung; Italien